Current Trends in the Study of Midrash - Bakhos, Carol (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This collection of essays by many of the leading scholars of midrash and rabbinics reflects the various current methodological approaches to the study of rabbinic scriptural interpretation. During the last three decades of the 20th century scholars in the field made significant forays into literary studies, interdisciplinary studies, and to some degree women's studies. This volume thus illustrates these trends, and highlights several fundamental studies, such as the origins of midrash, the making of critical editions, and the relationship of midrash to other forms of Jewish as well as non-Jewish exegesis. Situating midrash within the broader contexts of hermeneutics, rabbinics and postmodern studies, the volume as a whole presents the reader with a comprehensive view of the kinds of questions and issues scholars in the field are engaging.